Motivation and frustration in cardiology trial participation: The patient perspective - Meneguin, Silmara [UNESP]; Machado Cesar, Luiz Antonio (Universidade de São Paulo (USP), Hospital das Clínicas, 2012)
OBJECTIVE: The participation of humans in clinical cardiology trials remains essential, but little is known regarding participant perceptions of such studies. We examined the factors that motivated participation in such studies, as well as those that led to participant frustration.METHODS: Patients who had participated in hypertension and coronary arterial disease (phases II, III, and IV) clinical trials were invited to answer a questionnaire. They were divided into two groups: Group I, which included participants in placebo-controlled clinical trials after randomization, and Group II, which included participants in clinical trials in which the tested treatment was compared to another drug after randomization and in which a placebo was used in the washout period.RESULTS: Eighty patients (47 patients in Group I and 33 patients in Group II) with different socio-demographic characteristics were interviewed. Approximately 60% of the patients were motivated to participate in the trial with the expectation of personal benefit. Nine participants (11.2%) expressed the desire to withdraw, which was due to their perception of risk during the testing in the clinical trial (Group I) and to the necessity of repeated returns to the institution (Group II). However, the patients did not withdraw due to fear of termination of hospital treatment.CONCLUSIONS: Although this study had a small patient sample, the possibility of receiving a benefit from the new tested treatment was consistently reported as a motivation to participate in the trials.
Keywords: Motivation; Clinical trials; Frustration; Cardiology